1986
DOI: 10.1007/bf01454241
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac activity of the gliadin peptides CT-1 and CT-2

Abstract: The coeliac active peptide B 3142, which has been isolated from a peptic-tryptic digest of gliadin and which consists of 53 amino-acid sequences, was partially hydrolyzed with alpha-chymotrypsin. The two fragment peptides CT-1 (positions 1-22 of B 3142) and CT-2 (positions 23-53) were separated by high-performance liquid chromatography on octadecyl silica gel and purified by gel filtration on Biogel P2. The examination in the organ-culture test including 18 coeliac patients on normal diet and 7 control persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Of interest, these peptides are located in the amino-terminal region of gliadin, whereas our current T cell epitope resides in the carboxyl terminal region. Although several studies reported that the disease-promoting activity of gliadin is located in the first 55 amino-terminal residues of the molecule (11,12), there is also evidence that gliadin fragments in the carboxyl terminal region of gliadin can be toxic for CD patients (11,13,14). Peptide challenges with a peptide corresponding to residues 202-220 of gliadin, which displays high homology with the current HLA-DQ8-restricted T cell epitope, induced significant morphometric changes in the jejunal mucosa of one of four CD patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, these peptides are located in the amino-terminal region of gliadin, whereas our current T cell epitope resides in the carboxyl terminal region. Although several studies reported that the disease-promoting activity of gliadin is located in the first 55 amino-terminal residues of the molecule (11,12), there is also evidence that gliadin fragments in the carboxyl terminal region of gliadin can be toxic for CD patients (11,13,14). Peptide challenges with a peptide corresponding to residues 202-220 of gliadin, which displays high homology with the current HLA-DQ8-restricted T cell epitope, induced significant morphometric changes in the jejunal mucosa of one of four CD patients (15).…”
Section: Discussionmentioning
confidence: 99%
“…Wheat gliadins consist of o~/fl, % and co gliadins, all of which may cause disease (38). Considerable interest has been paid to peptides from the NH2-terminal region of cx-gliadin, since they have been shown to sustain the pathology of the established CD lesion using organ culture assays with biopsies from untreated CD patients (39,40). Interestingly, we have recently defined a T cell epitope in this region with DQ(oll*0501,fll*0201)-restricted T cells from the peripheral blood of a CD patient (Gjertsen et al, manuscript submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…First, since there is genetic variability between c~-gliadins (16)(17)(18), these findings do not allow us to definitively exclude that the T cells actually recognize peptides from this region. Second, although diseaserelevant epitopes can be found in the NH2-terminal region of ol-gliadin (39,40), other regions in both cx-gliadin (39,41) and other gliadins have been suggested to be implicated in the disease (38,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies implied that the N-terminal region of A gliadin was toxic to patients lenge. In 4 patients studied, all of whom had well-treated coeliac disease and had been receiving a gluten-free diet with coeliac disease [7,8].…”
Section: In Vivo Gluten Challengementioning
confidence: 99%
“…To assess the potential coeliac toxicity of amino acid sequenced A gliaal. [7,8] produced a series of N-terminal peptides of A gliadin that were tested by coeliac jejunal biopsy in vitro din peptides we compared the histology of biopsies taken at time 0 with those taken 6 h later after commencing chalorgan culture. The results of these studies implied that the N-terminal region of A gliadin was toxic to patients lenge.…”
Section: In Vivo Gluten Challengementioning
confidence: 99%